Health for All: a health literate, culturally competent and participative approach. (20th October 2021) - Banzola, S; Bandello, MA; Testi, A; Az, F; Clemente, G; Piazza, S; Mazza, M; Chiapponi, S; Costantino, R; Berghenti, F
Abstract: Background: Three micro projects, planned by the multidisciplinary team in a Primary Care setting targeting refugees and asylum seekers, aim at migrants' health, building strategies together with the private and social sectors involved, for a culturally competent and Health Literate approach, within the ICARE Project activities. Three different areas of work were identified: detecting barriers to migrants' management of prevention and care of Covid-19; preventing domestic accidents in children; improving the participation to screening programs among refugees and women victims of human trafficking. Objectives: The main objective is to improve migrants' engagement in health care and health promotion activities in a new context of living strongly influenced by the pandemic waves of Covid-19. The second objective is to enable a participative approach to migrants' health among intercultural mediators, nurses, paediatrician, infectious diseases specialist, psychologist, social workers and representatives of No Profit Organizations (NPOs) that support refugees and women victims of human trafficking within the "Oltre la Strada" Regional project. Results: A closed questionnaire assessing knowledge about prevention and management of Covid-19 has been carried out among 100 refugees and asylum seekers. A video on prevention of domestic accidents was made and translated in eleven languages as a result of a cooperation with intercultural mediators, to encourage questions during the educational meetings. Finally, a focus group was performed with NPOs in order to identify common areas of work, enabling a participative approach to improve migrants' engagement. Conclusions: The preliminary results reveal the need to approach migrants' health focusing on their participation through a multidimensional, person-centred, Health Literate and culturally competent cooperation. The outcomes from data analysis of the ongoing activities within the ICARE Project will be presented at the conference. Key messages: A multidimensional approach to migrants' health enables all stakeholders to learn from each others, improving the awareness about the relationship between health literacy and health outcomes. The cooperation between health, social and private sectors could be strategic for an organizational change towards a person-centred approach.